Accounting and the level of municipal internal control (Revista Brasileira de Contabilidade e Gestão, 2022)
This research aimed to control the level of Internal Control (CI) of the accounting sector of the Municipality of João Pessoa (PMJP). To this end, the profile of professionals in the Accounting Sector of the City Hall was surveyed; observed how the tasks are used in the aforementioned sector; and the degree of CI of the Accounting Sector of the Municipality referred to was verified. Regarding the composite and defined, it was prepared, being prepared, by 15 investigation staff and answered by 15 staff. In turn, an attempt at affirmative answers (“Yes” or “Partly”) were classified as within one time (excellent, good, regular and insufficient). In the results obtained, 20% of the questions had 100% of the CI questions, while the average of the answers indicated was 7.61%, whose parameter was only a percentage as the good ones. Therefore, it concludes that the Accounting Sector of the PMJP has a good internal control system, which can be modified and improved in the conduct of public management.
Keywords: accounting; internal control; town hall; accounting professional; accounting sector